2006
DOI: 10.1002/eji.200636259
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of CCL5 mRNA stores by post‐effector and memory CD8 T cells is dependent on transcription and is coupled to increased mRNA stability

Abstract: Immunological memory is associated with the display of improved effector functions by cells of the adaptive immune system. The storage of untranslated mRNA coding for the CCL5 chemokine by CD8 memory cells is a new process supporting the immediate display of an effector function. Here, we show that, after induction during the primary response, high CCL5 mRNA levels are specifically preserved in CD8 T cells. We have investigated the mechanisms involved in the long-term maintenance of CCL5 mRNA levels by memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…The stabilization of the mRNAs encoding important inflammatory mediators2057 constitutes an important paradigm of HuR's functions. Many inflammatory mediator mRNAs known to be regulated at the stability level58596061, and shown subjected to PARP1 regulation in the present study, are ARE-containing, such as Il1β , Cxcl1 , Cxcl2 and Ccl11 . Moreover, although there is no study addressing its stability, Il11 mRNA contains typical AREs in its 3′-UTR, and PARP1 inhibition resulted in a significant decrease in its mRNA stability as shown by plate-based real-time PCR arrays.…”
Section: Discussionsupporting
confidence: 49%
“…The stabilization of the mRNAs encoding important inflammatory mediators2057 constitutes an important paradigm of HuR's functions. Many inflammatory mediator mRNAs known to be regulated at the stability level58596061, and shown subjected to PARP1 regulation in the present study, are ARE-containing, such as Il1β , Cxcl1 , Cxcl2 and Ccl11 . Moreover, although there is no study addressing its stability, Il11 mRNA contains typical AREs in its 3′-UTR, and PARP1 inhibition resulted in a significant decrease in its mRNA stability as shown by plate-based real-time PCR arrays.…”
Section: Discussionsupporting
confidence: 49%
“…We have previously shown that in memory CD8 T cells Ccl5 expression is downregulated by IL-4 in a STAT6-dependent manner (6). Thus, we investigated whether STAT6 was also involved in the regulation of Nkg2d expression by IL-4 in T IM .…”
Section: Il-4 Regulates Nkg2d Expression In Memory Cd8 T Cells Via a mentioning
confidence: 93%
“…These elevated CCL5 mRNA levels have been observed in memory CD8 T cells generated in a variety of systems (4,5). They are maintained through constitutive transcription of the Ccl5 gene and increased stabilization of the mRNA (6). The increased efficiency of memory CD8 responses also arise from their lower activation threshold compared with naive cells.…”
mentioning
confidence: 91%
“…In addition, they contain 600 times more CCL5 mRNAs than naive F5 CD8 T cells (Fig. 2E), indicating that they have acquired the capacity to store CCL5 messengers, another functional feature of memory CD8 T cells (21)(22)(23)(24). Moreover, they express increased levels of T-bet and eomesodermin (Fig.…”
Section: F5 Cd44/122 Int Memory Cd8 T Cells Are Generated Under Sterimentioning
confidence: 93%